2014
DOI: 10.1111/j.1532-950x.2014.12095.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biomechanical Comparison of 3.5 String of Pearl Plate Fixation to 3.5 Locking Compression Plate Fixation in a Canine Fracture Gap Model

Abstract: The SOP construct was superior under bending static and cycling testing but the LCP construct was superior in static and cycling torsion testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 15 publications
2
20
2
Order By: Relevance
“…20 In a cadaveric study comparing SOP to the locking compressive plate (Synthes Vet; West Chester, Pennsylvania, United States), screw loosening was a mode of construct failure of the SOP in cyclical bending and torsion. 23 This was noted in four (2.4%) cases in this study. Two cases of screw loosening were incidental findings at postoperative radiography and two cases required implant retrieval.…”
Section: Discussionsupporting
confidence: 51%
“…20 In a cadaveric study comparing SOP to the locking compressive plate (Synthes Vet; West Chester, Pennsylvania, United States), screw loosening was a mode of construct failure of the SOP in cyclical bending and torsion. 23 This was noted in four (2.4%) cases in this study. Two cases of screw loosening were incidental findings at postoperative radiography and two cases required implant retrieval.…”
Section: Discussionsupporting
confidence: 51%
“…12,14 This discrepancy in results has been also suggested in different studies, where different bone material was used. 15,16 According to previous studies for a 40 kg dog while running at a trot, the force applied to hindlimbs would be $297 to 419 N (76-107% of body weight). 17 Under single cycle bending loading LCP and PLS plastically deformed at 419.5 and 282.2 N respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical advantages of the SOP implant from the previous studies were often attributed to the circular profile of the implant and higher associated area moment of inertia compared to rectangular implants [1315, 1921]. The difference in fracture model configuration in the presented study compared to the multiple aforementioned studies likely allowed less demonstration of the previously observed biomechanical advantages of the SOP plating system.…”
Section: Discussionmentioning
confidence: 83%
“…The clinically relevant conclusion of this study stated that due to differing plate construct properties inherent to diverse implant systems, identical approaches to fracture management and plate application cannot be applied [20]. In 2012, Malenfant and Sod compared SOP to LCP constructs in a cadaveric tibial diaphyseal fracture gap model and found that the SOP construct was superior under bending static and cycling testing, but the LCP construct was superior in static and cycling torsion testing [21]. Hutcheson et al compared bridging double plate SOP constructs to broad DCP constructs in a synthetic bone fracture gap model in 2015 and found that all biomechanical properties were significantly higher for the double SOP construct, but the actual differences were small [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation